2014
DOI: 10.3109/03009734.2014.922143
|View full text |Cite
|
Sign up to set email alerts
|

Predicting return to work among sickness-certified patients in general practice: Properties of two assessment tools

Abstract: Aim The purpose was to analyse the properties of two models for the assessment of return to work after sickness certification, a manual one based on clinical judgement including non-measurable information (‘gut feeling’), and a computer-based one.Study population All subjects aged 18 to 63 years, sickness-certified at a primary health care centre in Sweden during 8 months (n = 943), and followed up for 3 years.Methods Baseline information included age, sex, occupational status, sickness certification diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(21 reference statements)
2
4
0
Order By: Relevance
“…An important factor might be the timing of rehabilitation. In a United Kingdom review, it was found that in the first 3-6 weeks of sick leave, the likelihood of recovery and rapid sick leave conclusion is high, with or without healthcare intervention [29], as was found in another report from the present study [13]. After 6 weeks of sickness absence in workers, the risks of long- term incapacity increased by 10-20%, and after 6 months, there was only a 50% chance of returning to a previous job.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…An important factor might be the timing of rehabilitation. In a United Kingdom review, it was found that in the first 3-6 weeks of sick leave, the likelihood of recovery and rapid sick leave conclusion is high, with or without healthcare intervention [29], as was found in another report from the present study [13]. After 6 weeks of sickness absence in workers, the risks of long- term incapacity increased by 10-20%, and after 6 months, there was only a 50% chance of returning to a previous job.…”
Section: Discussionsupporting
confidence: 78%
“…Having access to the individual risk factor pattern of subjects on sick leave provides the possibility of early identification of patients who may not conclude their sick leave period as expected. In another previous report from this study, a further development of the risk factor concept was presented in the form of nomograms, where the risk of not concluding sick leave within the expected time might be obtained based on the three most important risk factors [13].…”
Section: Introductionmentioning
confidence: 99%
“…An important factor might be the timing of rehabilitation. In a United Kingdom review, it was found that in the first 3-6 weeks of sick leave, the likelihood of recovery and rapid sick leave conclusion is high, with or without healthcare intervention [30], as was found in another report from the present study [13]. After 6 weeks of sickness absence in workers, the risks of long-term incapacity increased by 10-20%, and after 6 months, there was only a 50% chance of returning to a previous job.…”
Section: Discussionsupporting
confidence: 78%
“…A comprehensive literature search strategy adapted from a 2017 review [2] was performed using Medline and yet, no studies were identified which categorized prognostic variables and used an analytical approach resembling the order of information obtained in a clinical setting. For this reason, direct comparison with previous studies was not possible, but some studies reported measures that can be compared with the current study [33, 34]. In a Norwegian study [33], the sickness absentees’ own prediction of sick leave duration ≥26 weeks yielded a slightly better PPV (0.78) than any of the models in the current study.…”
Section: Discussionmentioning
confidence: 78%
“…Rehabilitation professionals in another study [34] predicted the chance of RTW based on sick leave duration, reason for sick leave, unemployment, age > 45 years, female sex and ‘gut feeling’. Their prediction was concordant with actual RTW in 73% and thus lower than the specificity estimates of all four models in the current study.…”
Section: Discussionmentioning
confidence: 99%